Adapting Web Content Based On User Connection Speed To Ensure Response Time - Rostami, Reza; Kian Chiew, Thiam (Malaysian Journal of Computer Science, 2013)
Response time to download a Web page is mainly determined by network bandwidth and the size of the page. With the notion of tolerable waiting time (TWT), this response time should be confined below a threshold value for user satisfaction. Nevertheless, users connect to the Internet with different connection speeds, causing variable response times in relation to different connection speeds. This paper presents a Web content adaptation and delivery technique based on user connection speed in order to download the page within a configurable time threshold. The technique not only ensures Web page response time meets the desired threshold value, but also preserves overall page quality by preventing Web page items to have inconsistent quality.